(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The number of issues related with oral, parenteral, rectal and different routes of drug administration. The interest of pharmaceutical researchers has expanded towards investigating the conceivable outcomes of nasal delivery of different medications. Nasal drug delivery system is ordinarily known for the treatment of nearby illnesses like cold, hack, rhinitis, and so on. Endeavors have been made to convey different medications, particularly peptides and proteins, through nasal route for initial use; using the standards and ideas of different nanoparticulate sedate conveyance frameworks utilizing different polymers and retention advertisers. The use of medications into nanoparticles may be a promising methodology, since colloidal plans have been appeared to shield them from the corrupting milieu in the nasal pit and encourage their vehicle over the mucosal obstructions. The intranasal delivery is gone for improving medication bioavailability for fundamental medications, as assimilation diminishes with expanding molecular weight, and for medications, which are powerless to enzymatic degradation, for example, proteins and polypeptides.